The analysis of financial performance of Bank Kerjasama Rakyat Malaysia Berhad / Mohammad Farouk Al-Ambri Abd Ghani - Abd Ghani, Mohammad Farouk Al-Ambri (Faculty of Business and Management, 2010)
The focus of this study is to examine the financial performance of Bank Kerjasama Rakyat Malaysia Berhad. Financial performance is a subjective measure of how well a firm can use assets from its primary mode of business and generate revenues. This study will focus on the company financial statement for the past five year’s period range from 2005 to 2009. The objectives of this study are to analyze company performance by using ratio analysis and to identify company trends by using common size analysis. This study uses data from the company financial statement consist of balance sheet and income statement. The researcher will calculate using five ratio analysis which are Profitability Ratio, Liquidity Ratio, Capital Structure and Solvency Ratio, Return on Investment Ratio, and Asset Utilization Ratio in order to determine the financial performance of the company. Based on the findings, the company will need to improve on some ratio such as quick ratio, total debt to equity ratio, return on assets ratio, and total asset turnover ratio in order to ensure that the company is able to maintain their profitability and able to expended their business in the future.